Twelve Texas Aggie War Heroes : From World War I to Vietnam. - Woodall, James R.; Darling, Thomas G. (College Station : Texas A & M University Press, 2015)
Following on the success of Texas Aggie Medals of Honor, James R. Woodall now returns with a new book that focuses on the military service by graduates of Texas A&M University from World War I to Vietnam. Of the tens of thousands of Aggies who served in the nation?s military, Woodall has selected twelve individuals who stand out as singular examples of bravery and heroism.Twelve Texas Aggie War Heroes tells each serviceman?s story in a concise, engaging manner. Some subjects, such as Earl Rudder and James Hollingsworth, will be familiar to readers. But Woodall also introduces us to less familiar but no less notable men as well, from A. D. Bruce?s march from the trenches of France and the crossing of the Rhine in World War I to Bob Acklen?s three tours in Vietnam. In addition to the twelve chapters focusing on these remarkable individuals, Woodall provides an extensive set of appendixes that include the relevant citations for each serviceman as well as larger lists of Aggies who were awarded the Distinguished Service Cross, Navy Cross, or Air Force Cross.
CONTENTS, pg 2; FOREWORD; PREFACE; ACKNOWLEDGMENTS; 1. Defender of Corregidor; 2. Father of Fort Hood; 3. Doolittle Raider; 4. Rangers Lead the Way; 5. Flying Tiger Ace; 6. Battlefield and Congressional Tiger; 7. Highpockets, One Tough Marine; 8. Sole Survivor of Torpedo Squadron 8; 9. Danger 79er; 10. Aggie Ace of Aces; 11. Kyle Field Star, Battlefield Hero; 12. Three Tours Are Enough; APPENDIX 1; APPENDIX 2; NOTES; BIBLIOGRAPHY; INDEX; MAPS.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Agricultural and Mechanical College of Texas -- Alumni and alumnae -- Biography; Texas A & M University -- Alumni and alumnae -- Biography; Agricultural and Mechanical College of Texas. -- Corps of Cadets -- Biography; Texas A & M University. -- Corps of Cadets -- Biography; Agricultural and Mechanical College of Texas; Agricultural and Mechanical College of Texas. -- Corps of Cadets; Texas A & M University; Texas A & M University. -- Corps of Cadets; Veterans -- Texas -- Biography; Heroes -- Texas -- Biography; United States -- History, Military -- 20th century; Anciens combattants -- Texas -- Biographies; Héros -- Texas -- Biographies; États-Unis -- Histoire militaire -- 20e siècle.; EDUCATION -- Higher; Heroes; Universities and colleges -- Alumni and alumnae; Veterans; Texas; United States; 1900-1999; Electronic books; Biographies; Military history